RORγt inverse agonists demonstrating a margin between inhibition of IL-17A and thymocyte apoptosis - Mia Collins; Rikard Pehrson; Hanna Grindebacke; Agnes Leffler; Marie Ramnegård; Helena Rannikmäe; Nina Krutrök; Linda Yrlid; Charlotte Pollard; Ian Dainty; Frank Narjes; Stefan von Berg; et al. (PLoS ONE, 2025)
Multiple genetic associations suggest a causative relationship between Th17-related genes coding for proteins, such as IL-17A, IL-23 and STAT3, and psoriasis. Further support for this link comes from the findings that neutralizing antibodies directed against IL-17A, IL-17RA and IL-23 are efficacious in diseases like psoriasis, psoriatic arthritis and ankylosing spondylitis. RORγt is a centrally positioned transcription factor driving Th17 polarization and cytokine secretion and modulation of RORγt may thus provide additional benefit to patients. However, RORγt also plays a role in the normal development of T cells in the thymus and genetic disruption of RORγt in the mouse leads to the development of lymphoma originating in the thymus. Whilst it is not established that down-regulation of RORγt activity would lead to the same consequence in humans, further understanding of the thymus effects is desirable to support progress of this target as a potential treatment of Th17-driven disease. Herein we present the characterisation of recently disclosed RORγt inverse agonists demonstrating target engagement and efficacy in vitro and in vivo against Th17 endpoints but requiring higher concentrations in vitro to affect thymocyte apoptosis.